2005
DOI: 10.1091/mbc.e05-04-0301
|View full text |Cite
|
Sign up to set email alerts
|

ERK Phosphorylates p66shcA on Ser36 and Subsequently Regulates p27kip1Expression via the Akt-FOXO3a Pathway: Implication of p27kip1in Cell Response to Oxidative Stress

Abstract: Mice deficient for p66shcA represent an animal model to link oxidative stress and aging. p66shcA is implicated in oxidative stress response and mitogenic signaling. Phosphorylation of p66shcA on Ser36 is critical for its function in oxidative stress response. Here we report the identification of ERK as the kinase phosphorylating p66shcA on Ser36. Activation of ERKs was necessary and sufficient for Ser36 phosphorylation. p66shcA interacted with ERK and was demonstrated to be a substrate for ERK, with Ser36 bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
50
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 53 publications
6
50
0
1
Order By: Relevance
“…Pretreatment by ICA induced significantly activation of ERK and AKT. There are reports that indicated ERK was involved in H 2 O 2 -induced cell response (Hu et al, 2005). In the present study, the concentration of homocysteine was up to 400 μM, thus we deduced that the increase of Figure 6.…”
Section: Discussionsupporting
confidence: 50%
“…Pretreatment by ICA induced significantly activation of ERK and AKT. There are reports that indicated ERK was involved in H 2 O 2 -induced cell response (Hu et al, 2005). In the present study, the concentration of homocysteine was up to 400 μM, thus we deduced that the increase of Figure 6.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have reported the association between ERK, p66 shc adaptor protein 1 (p66shcA) and FOXO3. The phosphorylation of p66shcA Ser36 is required for phosphorylation of FOXO3a, which can be induced by ERK1/2 (48). In cardiac fibroblasts, activation of ERK1/2 can directly phosphorylate FOXO3a and regulate its activity, and ERK1/2 can also phosphorylate Skp2 in the same manner.…”
Section: Mammalian Sterile 20-like Kinase (Mst) and Jun-n-terminal Kimentioning
confidence: 99%
“…In cardiac fibroblasts, activation of ERK1/2 can directly phosphorylate FOXO3a and regulate its activity, and ERK1/2 can also phosphorylate Skp2 in the same manner. Notable, a report previously demonstrated that Skp2 can inhibit the activity of FOXO3a and promote its degradation (48,49). SGK is another link between MAPK and FOXO proteins.…”
Section: Mammalian Sterile 20-like Kinase (Mst) and Jun-n-terminal Kimentioning
confidence: 99%
“…p66ShcA has emerged as a genetic determinant of longevity in mammals (10) that controls mitochondrial metabolism and cellular responses to oxidative stress, aging, and apoptosis. The potent stress response regulator Foxo3A is a downstream target of p66ShcA redox signals that phosphorylate key regulatory sites, inhibiting transcription of Foxo3A stress-related gene products (11,12). Because phosphorylation at a critical Ser-36 residue activates p66ShcA redox activity (13), mutation at this site should inhibit transmission of reactive oxygen species (ROS)-dependent signals…”
mentioning
confidence: 99%